Automating Estimation of Battery State of Charge Using Experimental Data in MatLab - Pradeep Vibhuti (Newinera Publisher, 2020)
This paper explains how to estimate the state of charge (SOC) of a battery using implementation of characteristics governing equations and and lookup table. Look up table containing experimental data like charging resistance, discharging resistance and battery voltage in an excel sheet. Estimation of state of charge as a function of voltage is simulated with the help of experimental data in the form of lookup table in Matlab simulink and mscript. A 4V battery was charged and discharged at a 2.3 ampere for an hour. Matlab simulunk model with m.scipt is developed to determine terminal voltage and state of charge is obtained at any given time.